The Implementation of Digital Picture Text Story Media in Developing Character Education - Badruli Martati; Idhoofiyatul Fatin; Dewi Setianingsih (Fakultas Keguruan dan Ilmu Pendidikan (FKIP), Universitas Lancang Kuning, 2025)
Integrating character values with school subjects can be used as powerful medium in the academic environment or classroom. By underscoring illustrated stories with digital technology will help teachers to foster students’ essential attitudes and characters education in elementary level. The purpose of the study is to find students characters in education. The research method used was quantitative with the type of pre-experimental one group post-test only design. The third students were included in the category of concrete operational development, which could help their imaginations in delivering stories, pictures or other things. The research finding showed that the use of illustrated stories with digital technology greatly helped the students' understanding. Instilling character values was carried out by teachers by inserting in the school subjects. Assessment of mutual cooperation attitudes as much as 89% of students have appeared in the learning process. This means that they were able to cooperate with group members and were open to accepting their friends' ideas. As many as 100% of students showed an attitude of responsibility, they were able to work on tasks according to the steps of instructions from the teacher so that they could accomplish the tasks on time. As many as 82% of students showed an independent attitude, were able to do tasks without much dependence on friends or teachers. As the conclusion, the use of picture story text media with digital technology has proven effective in developing characters education among elementary school students.